PENGARUH LIKUIDITAS, UKURAN PERUSAHAAN, STRUKTUR MODAL DAN PERTUMBUHAN PENJUALAN TERHADAP NILAI PERUSAHAAN - Zeffa Azzahra Yulitha (Jurnal Riset Multidisiplin Edukasi, 2026)
The research objective is to examine the impact of liquidity, company size, capital structure, and sales growth on company value in the transportation industry listed on the Indonesia Stock Exchange (IDX) from 2018 to 2021. Researchers used a sample of companies in the transportation sector listed on the IDX in 2018 to 2021. In the study, the population used consisted of 48 companies. The researcher applied a purposive sampling technique to select the research sample. The selection process was based on predefined criteria, resulting in 9 companies and a total of 36 financial reports. The research data consists of secondary data which is financial report data and annual reports. This study uses a data analysis approach that involves the use of descriptive statistics, followed by an examination of classical assumptions. These assumptions include several tests, including tests for normality, multicollinearity, autocorrelation, and heteroscedasticity. F-testing, t-testing, and testing the coefficient of determination are used in testing hypotheses. The research findings indicate that firm value is simultaneously influenced by liquidity, firm size, capital structure, and sales growth. Firm value has a positive influence on liquidity, capital structure, and sales growth partially. Meanwhile, firm value has a partial negative effect on firm size.